2020
DOI: 10.29298/rmcf.v11i62.759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación financiera y económica de un sistema silvopastoril intensivo bajo riego

Abstract: Los sistemas silvopastoriles son importantes para la sustentabilidad ambiental y económica de los productores que los utilizan. Por lo anterior, el objetivo de este trabajo fue evaluar la rentabilidad financiera y económica del sistema silvopastoril intensivo Leucaena leucocephala en asociación con pradera bermuda cruza dos (Cynodon dactylon), bajo riego en la producción de becerros de engorda en el sur de Sinaloa; a fin de contribuir con información a la sustentabilidad productiva, económica y ambiental en re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…compared with the grass monocultures, which are rather common in the Colombian cattle landscape [ 55 , 153 ]. This coincides with the study of Cuevas-Reyes et al [ 94 ] who found that the profitability indicators of a SPS with Leucaena leucocephala and Cynodon dactylon significantly improve when their carbon capture potential is considered and monetized. Likewise, it coincides with Bussoni et al [ 93 ], whose findings suggest that the reduction of CO 2eq.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…compared with the grass monocultures, which are rather common in the Colombian cattle landscape [ 55 , 153 ]. This coincides with the study of Cuevas-Reyes et al [ 94 ] who found that the profitability indicators of a SPS with Leucaena leucocephala and Cynodon dactylon significantly improve when their carbon capture potential is considered and monetized. Likewise, it coincides with Bussoni et al [ 93 ], whose findings suggest that the reduction of CO 2eq.…”
Section: Discussionsupporting
confidence: 91%
“…Although the assessment of financial viability of SPS is increasingly gaining importance in scientific literature, research related to the economic profitability and impacts of cattle production systems has been traditionally focused on the evaluation of implementing improved forages, mostly as monocultures [ 56 , 57 , 68 , 69 , 80 , 90 , 91 ], or grass-legume associations [ 55 , 92 ]. Likewise, only few recent studies have focused on providing estimates of the economic-environmental benefits of implementing SPS [ 93 , 94 ].…”
Section: Insights Into Literature On Economic and Environmental Evalu...mentioning
confidence: 99%
See 2 more Smart Citations